Horace on Diseases - Grzelak-Krzymianowska, Adriana (Collectanea Philologica, 2023)
Quintus Horatius Flaccus, vividly portrayed for us in his works both a picture of contemporary society and the world of his convictions and beliefs. Among the many researched issues in his work, there are some that still need to be addressed. These include references of a medical nature. The purpose of this article is to point out numerous of Horace’s medical references which give clues as to what health problems plagued Augustan Rome in particular.